Geogebra Software And Playful Strategies In Mathematics Learning In Students Of A State Educational Entity Of Piura, 2023 - Mario, Rufino Sosa; Angélica, Atoche-Silva, Luz; Manuel, Sandoval Peña, José; Carmen, Sandoval Chunga, María; Socorro, García Paz, Elizabeth del (Migration Letters, 2024)
The objective of the investigative study was to determine the effect of GeoGebra Software and playful strategies on mathematics learning in students of a state educational entity in Piura, 2023. The research was quantitative, applied and pre-experimental in design. The sample was 48 students, to whom a written test "I demonstrate my learning in mathematics" was administered, which has a KR-20 reliability of 0.823 and expert criterion validity with an Aiken V of 0.88. The results after the application of the program are positively evident in the achievement levels. Before the program, 85.42% of students were below expected achievement (Start and process) and after, 66.67% were in expected achievement and 8.33% in outstanding achievement. In the hypothesis testing, a significance of less than 5% (p<0.05) was obtained, determining the effect of the program in the four dimensions: solves problematic quantity situations; of regularity, equivalence and change; of form, movement and location; and data management and uncertainty, concluding that the use of GeoGebra software and playful strategies have a significant effect on mathematics learning.